Aplicación de macrorreglas para mejorar la comprensión lectora en los estudiantes de primer grado de secundaria en una institución educativa del distrito de Chicama, año 2020 - Iparraguirre Contreras, Segundo Freddy (2021)
The purpose of this research was to determine the influence of the application of macro-rules on reading comprehension in first grade high school students of the I.E. “Santo Domingo de Guzmán”, Chicama, 2020. For this purpose, a study with a quantitative approach was developed, an explanatory level with a pre-experimental design, using a sample made up of 25 students from section B of the first grade of secondary school, at who were given eight learning sessions on the use of macro-rules, as measurement instruments, the questionnaire and the objective test were used to measure the level of reading comprehension before and after the use of the learning sessions. After data collection and information processing, the Student's t test was applied where a test statistic was obtained (t = -13.591) and a significance value (p = 0.000) being less than the maximum permissible error of 0.05, for There was sufficient statistical evidence to conclude that there is a significant influence of the application of macro-rules on the level of reading comprehension in first-grade high school students from the educational institution mentioned above.